Late Prehistoric Oneota population movement into the central Plains - Ritterbush, Lauren W.; Logan, Brad (My University, 2000)
The White Rock phase is an intrusive Late Prehistoric archaeological complex in the central Plains. It shows clear ties to the Oneota tradition of the upper Midwest. Population movement best explains the presence of this Oneota complex in the Plains. Interpretations of seasonal mobility or migration are evaluated through analysis of White Rock phase assemblages. Evidence for gardening and lithic material use patterns suggest permanent or year-round occupation of the central Plains resulting from the Oneota migration.
Keywords: White Rock phase; Oneota; Late Prehistoric; Migration; Lithic raw materials